Then there was you [large type] - Isaac, Kara (Center Point Large Print, 2019)
"Paige McAllister leaves her life in Chicago to move to Sydney, Australia where she becomes a logistics planner for one of Australia's biggest churches. Her boss's son, Josh Tyler fronts a top-selling worship band. When Josh and Paige are thrown together to organize his band's next tour, the sparks fly"--